Three-dimensional graphene-reinforced Cu foam interlayer for brazing C/C composites and Nb. (July 2017) - Wang, Zeyu; Wang, Gang; Li, Manni; Lin, Jinghuang; Ma, Qiang; Zhang, Aotian; Zhong, Zhengxiang; Qi, Junlei; Feng, Jicai
Abstract: Brazing C/C composites to Nb is often associated with high residual stress in this research, which results in low-strength joints. To overcome this problem, here we report a novel type of three-dimensional graphene-reinforced Cu foam (G-Cu foam) composite fabricated using chemical vapor deposition. This G-Cu foam was used as an interlayer for brazing C/C composite and Nb. Results show that high-quality graphene was evenly introduced in the brazing seam without agglomeration with the help of Cu foam substrate, which has a porous structure with an interconnected 3D scaffold. Moreover, wetting analyses revealed that the obtained graphene played a key role in retarding the metal atoms diffusion and consequently impeding the collapse of the Cu foam skeleton at brazing temperature. Furthermore, the extremely low coefficient of thermal expansion (CTE) of graphene and the good plastic deformation capacity of Cu foam are both conducive to reducing the thermal residual stress during the cooling process. By exerting the synergistic strengthening effect of both graphene and Cu foam, the brazed joint was effectively enhanced. The average shear strength of the joint brazed with G-Cu foam interlayer is ∼43 MPa. Graphical abstract: